Relação entre sistemas de controle estratégico e comprometimento organizacional: um estudo em uma empresa pública do setor elétrico - Santos, Lucas Cristiano Fath (2020)
Control systems have been used as a management practice to control and monitor the implementation of guidelines established by the organization. Studies in this field of research are growing. However, there is little research associating the dimensions of the Simons (1995) levers of control model with the three-dimensional organizational commitment model of Meyer and Allen (1991). Thus, considering that the levers of control can positively influence organizational commitment, this study aims to evaluate the relationships between the strategic levers of control proposed by Simons (1995) and the organizational commitment in a public company of the electric sector. Data collected through a survey and analyzed through correlations revealed positive associations levers of control and organizational commitment. Finally, suggestions for improvements were proposed, both of the levers of control that obtained low yields in its implementation, as well as from the measurement of organizational commitment levels, proposed new directions that allow to increase the commitment levels of the organization's employees, object of this study.